Figurative Language in Symbolic Space – Interpretation and Imagination in Understanding Meanings - Lubowicka, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
The paper examines the philosophical account of language arising from the so-called rhetorical turn that occurred in the seventies of the twentieth century and was authored mainly by Paul de Man. Paul de Man emphasises rhetorical mechanisms at work in language, which means that the process of understanding is essentially tropological in nature and interpretation captures and pays close attention to the conventions of rhetoric. How do meanings operate in a language which is rhetorical? Metaphor as a basic rhetorical trope, together with symbol and image, have been chosen to illustrate how meanings are constructed and understood in a language thought of as being rhetorical. An analysis of metaphor, symbol and image shows a fundamental role interpretation and imagination play in understanding meanings. The understanding of meanings requires reference to the linguistic code operating in the symbolic space, but also allows for subjective and creative interpretation.
Keywords: image; imagination; interpretations; metaphor; rhetoric; rhetorical turn; symbol